Native plants from the Amazon region: an integrative review of their application in herbal medicine (Research, Society and Development, 2021)
The use of medicinal plants is an ancient practice, being part of human evolution, being considered the first therapeutic resources in society due to their pharmacological potential. Given this context, this study sought to carry out an ethnobotanical survey on the knowledge and use of medicinal plants in the Amazon, demonstrating the importance of regional plants with pharmacological action for the population. Documentary source research was carried out, with an integrative literature review, through articles published on the topic in question. Based on the analysis and discussion of the results, the studies reveal the importance of using medicinal plants even in environments with high purchasing power, aiming to obtain further studies on medicinal plants from the Amazon region that have pharmacological action, this work through databases and Using descriptors, 20 articles were used for an integrative review of the topic, setting up a synoptic table with the main results of the integrative review. It is important to emphasize that the use of medicinal plants is still an important resource used to maintain the health of many poor communities, where they are used for common health treatments, considering that the cost is more accessible to the population, compared to medicines obtained by chemical synthesis, which are generally more expensive due to the technological patents involved.